Report of the Independent Panel on Safeguards Assessments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
In its March 2002 review of the Safeguards Assessments (SA) policy, the Executive Board of the IMF indicated that an independent panel should be involved in the next review of the SA policy in early 2005. To meet this requirement, a panel of four deputy central bank governors from different regions was convened (see Attachment I). The panel was asked to determine whether safeguards assessments have been successful in meeting their stated objectives, and what, if any, improvements could be made to the safeguards policy and process going forward. The panel's terms of reference are included as Attachment II.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet